PENGARUH PENERAPAN THINK-TALK-WRITE BERBASIS WEB LIVEWORKSHEET PADA MATERI STRUKTUR DATA DAN ALGORITMA TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS X AKL SMKN 1 KUPANG - Angul, Angelina; J. Taku Neno, Katrin; Enstein, Jhon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted to examine the effect of the Think-Talk-Write (TTW) learning model assisted by the Liveworksheet web platform on the critical thinking skills of Grade X Accounting and Finance (AKL) students at SMK Negeri 1 Kupang in the topic of Data Structures and Algorithms. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest-Posttest Design. The research sample consisted of 34 students selected from Grade X AKL 2. Data were collected through pretest and posttest instruments measuring students' critical thinking skills and analyzed using descriptive statistics, normality testing, and the Paired Samples t-Test. The results showed a substantial improvement in students' critical thinking skills after the implementation of the TTW model assisted by Liveworksheet. The mean pretest score increased from 42.00 to 86.21 on the posttest. The normality test indicated that both datasets were normally distributed (Sig. > 0.05). Furthermore, the Paired Samples t-Test produced a t-value of -13.167 with a significance value of p < 0.001, indicating a statistically significant difference between students' pretest and posttest scores. Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. It can be concluded that the implementation of the Think-Talk-Write learning model assisted by the Liveworksheet web platform has a significant positive effect on improving students' critical thinking skills in Informatics learning, particularly in the topic of Data Structures and Algorithms.